STRATEGI HUKUM DALAM MENINGKATKAN INVESTASI UNTUK SEKTOR USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI INDONESIA - Suhanti, Kartika Ayu (Jurnal Hukum Positum, 2024)
The legislation governing foreign investment, as outlined in Law Number 25 of 2007 concerning Capital Investment, is a political creation aimed at providing equal treatment to investments from any nation that chooses to invest in Indonesia. This regulation offers numerous advantages for foreign investors, such as tax exemptions or reductions, repatriation of capital, and streamlined licensing processes. However, the political implications of this law for Micro, Small, and Medium Enterprises (MSMEs) run counter to the principle of economic democracy enshrined in Article 33 of the 1945 Constitution of the Republic of Indonesia. Economic democracy mandates the fulfillment of fundamental rights for all Indonesian citizens, including MSMEs, without any exclusion of individuals. In contrast, the provisions of trade liberalization, rooted in capitalist ideology, may constrain these basic rights and favor those who can compete and benefit from international trade provisions. Meanwhile, MSMEs still require policy support and affirmation from the government.